Диверсия: [роман] / Андрей Ильин - Ильин Андрей Александрович (Вне закона, 1997)
Экземпляры: ф.6 (2003) / Инвентарный номер: 39802 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: И 46 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44